Festribal: um diálogo sobre a cultura indígena e sobre arquelogias em Juruti - Pará - AMAZONAS, Indira Barbara Lima (Universidade Federal do Oeste do Pará, 2023)
In Juruti, Pará, every year the Festribal takes place, a festival considered the greatest cultural heritage of the municipality, where two groups called Munduruku Tribe and Muirapinima Tribe compete for a title through their presentations of dances, allegories, theatrical arts, among others, focused on indigenous culture themes. Their names carry the narrative of the people of Juruti about their origins. The archaeological material found in the region aids in validating this discourse. Therefore, it is important to reflect on how people in the present interact with the material culture of the past in Juruti from a public archaeology perspective, and also to analyze how the discipline of archaeology and the appreciation of indigenous culture have been disseminated through Festribal. For this purpose, a bibliographic survey and interviews were conducted to obtain an overview of both Juruti's history and the festival, as well as supplementary information. As a result,we have the Festribal as an important mean of dialogue between the population of Juruti, indigenous culture, and archaeology.